Coping Mechanisms and Quality of Life Among the Elderly in Gandus Sub-District, Palembang City - Yona Wia Sartika Sari; Evi Martha; Sudijanto Kamso; Dadan Erwandi Erwandi; Kartini Ruswandi; Dedi Sandra (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2025)
The decline in the physical and mental condition of the elderly, along with age, resulted in the elderly being very vulnerable to various diseases. The use of coping mechanisms has a crucial role in influencing both individual physical and psychological well-being. This study aimed to investigate the relationship between coping mechanisms and quality of life among the elderly. This research was conducted in the Gandus District of Palembang City. This quantitative study employs a cross-sectional design, utilizing simple random sampling as the sampling technique. Data collection was conducted through interviews with questionnaires administered to 110 elderly respondents. This study found that of respondents with a good quality of life, 75% used adaptive coping. The logistic regression results showed a significant correlation between coping mechanisms (p-value = 0.001) with OR (95% CI) = 5.540 (2.068-14.844), education (p-value = 0.003 with OR (95% CI) = 4.497 (1.646-12.285), employment (p-value = 0.005) with OR (95% CI) = 4.976 (1.644-15.059) with quality of life of the elderly. Adaptive coping mechanisms play a role in enhancing quality of life. This association was stronger among elderly individuals with higher education and employment.